P197 Obtaining a Tissue Diagnosis in Lung Cancer Patients with Poor Performance Status May Not Influence Treatment or Confer Survival Benefit. (19th November 2012) - Maclay, JD; Farley, J; Tweed, C; Horst, J van der; Bicknell, S; Milroy, R
Abstract : Introduction: Further investigation and treatment following a radiological diagnosis of lung cancer is influenced by the fitness of a patient. A pragmatic approach to investigative procedures is often adopted based on the risks and benefits. Another consideration is whether tissue diagnosis is necessary for anticipated future treatment. Tissue diagnosis is usually deemed essential prior to administration of radical radiotherapy and chemotherapy, but less so for palliative radiotherapy. Methods: All patients with lung cancer diagnosed in North Glasgow in 2009 and 2010 were prospectively recorded in a registry. We subsequently investigated the relationships between WHO performance status (PS) and tissue diagnosis, treatment and survival. Patients were followed up for at least 18 months after entry into the registry. Results: 1190 patients were diagnosed with lung cancer during the study period and clinical details were recorded at a multidisciplinary meeting. PS was recorded in 91%. Overall, tissue diagnosis was achieved in 76% of patients. Tissue diagnosis was achieved in 98% of patients with PS 0 following diagnostic procedure or surgery (table 1 ). Nearly 90% of these patients underwent chemotherapy, surgery or radical radiotherapy. Tissue diagnosis was attempted in 71% and 46% of PS 3 and 4 respectively. Of these patients, treatment was influenced by tissue diagnosis in 15% and 0%. Survival was compared in these patients and there was no difference between patients with a PS of 3 or 4 that had tissue diagnosis attempted and those that did not (median days (interquartile range); PS3: tissue 53 (19–138) vs no tissue 59 (17–156); PS4: 18 (8–36) vs 16 (6–32)). Conclusions: A significant percentage of patients with performance status 3 and 4 undergo diagnostic tests to establish a tissue diagnosis. However, treatment is only influenced by this in a minority of cases. Considering likely future treatment is important when pursuing a tissue diagnosis in these patients. In addition, attempting tissue diagnosis in these patients did not confer any survival benefit.